Mobile LiDAR, geoinformation technologies and crowdsourcing for the documentation and preservation of cultural heritage objects in territorial communities - Koshel, A.; Kolhanova, I.; Poltavets, A.; Yukhymiuk, V. (Land Management, Cadastre and Land Monitoring, 2025)
The article substantiates the integrated use of LiDAR technologies, geographic information systems (GIS) and crowdsourcing approaches for identifying, recording and monitoring historical and cultural heritage sites within local communities. It is emphasised that in the context of military action, urbanisation pressure and territorial transformations, cultural heritage is considered an important resource for sustainable development in accordance with UNESCO approaches and the World Heritage Sustainable Development Policy (2015). It is shown that modern LiDAR systems, including sensors built into smartphones, provide dense point clouds and three-dimensional models of objects with sufficient accuracy to solve a significant part of the tasks of documentation and operational monitoring, although they are inferior to high-precision ground and airborne laser scanners. Particular attention is paid to the hypothesis regarding the possibility of creating 3D models of cultural heritage objects using common smartphone models with built-in LiDAR sensors and assessing the accuracy of measurements of such models. To test the approach, a field scan of the local hydrological natural monument "Natural Spring" within the Shpanivska territorial community of the Rivne region was performed using a smartphone with a LiDAR module. Processing point clouds in Polycam, AutoCAD, PIX4D, 3ds Max, and Blender software made it possible to build a 3D model of the structure and estimate the relative error in measuring linear dimensions. For a reference section 210 cm long, the relative measurement error was 2.04%, which is consistent with the results of international studies on the accuracy of mobile LiDAR sensors, which demonstrate millimetre-centimetre accuracy for small objects and centimetre-decimetre errors in complex environments. The technical limitations of mobile LiDAR (limited scanning range, reduction in density and accuracy with distance, sensitivity to surface properties, influence of the operator’s scanning trajectory, need for control measurements) were analysed and the prospects for their application for mass crowdsourced data collection on heritage objects were demonstrated. Based on an analysis of geocrowdsourcing experience, it is argued that the combination of the prevalence of smartphones, mobile LiDAR sensors and web GIS creates the conditions for the formation of distributed information systems for recording, monitoring and preliminary assessment of the condition of monuments at the level of local communities, provided that data standardisation and quality control procedures are implemented. Keywords: geoinformation technologies, Lidar, amalgamated territorial community, historical and cultural heritage, sustainable development.